Maswandi Criminal Liability For Corruption By Public Officials: Analysis Of Decision No. 141/Pid.Sus-TPK / 2024 / PN Mdn: Criminal Liability For Corruption By Public Officials: Analysis Of Decision No. 141/Pid.Sus-TPK / 2024 / PN Mdn - Maswandi; Nanang Tomi Sitorus; Ariman Sitompul (Faculty of Law, Universitas Pekalongan, 2025)
Corruption committed by public officials is a serious violation of the integrity and trust of the public in the state administration. This study analyzes criminal liability for corruption perpetrators in their capacity as public officials through the case study of Decision No. 141/Pid.Sus-TPK / 2024 / PN Mdn. Juridical-normative approach and Decision Analysis become the basis in assessing how the application of criminal elements and the principle of responsibility. The results showed that public officials can be held criminally liable in full if proven to commit unlawful acts with awareness and bad faith. This decision confirms the importance of judicial independence in combating corruption.